Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.33650/al-tanzim.v6i3.3619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Motivation and Discipline on The Performance of The Leading Teachers of Madrasah

Abstract: This article aims to determine the effect of motivation and work discipline on MA Unggulan Hikmatul Amanah Pacet. Respondents in this study were all teachers of the Supreme Court of Hikmatul Amanah Pacet, totaling 39 people. The results of the study found that: 1) The effect of work motivation on the performance of MA Hikmatul Amanah teachers was 23.9%, with a research t value of 1.589 < t table of 1.687 and a significant value of 0.121 > 0.05; 2) The effect of work discipline on Hikmatul Amanah's teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…These variations result in confusion in concluding how important the role of motivation is in teacher academic performance. Besides that Suprihatin et al, (2022) the influence of motivation on performance shows that the causal correlation with employee performance is a positive relationship.…”
Section: Summary Effectmentioning
confidence: 97%
“…These variations result in confusion in concluding how important the role of motivation is in teacher academic performance. Besides that Suprihatin et al, (2022) the influence of motivation on performance shows that the causal correlation with employee performance is a positive relationship.…”
Section: Summary Effectmentioning
confidence: 97%
“…In the educational environment, this leadership includes the role of the head of the madrasa. In this context, the head of the madrasa is used as someone who manages the madrasa exclusively and gives performances to others to carry out managerial skills with skills that are in accordance with the provisions of the madrasa (Suprihatin, 2022).…”
Section: D) Motivating Educators In Research Madrasasmentioning
confidence: 99%
“…This study focuses on examining the influence of competence and motivation on lecturer performance. Although studies on this topic have been conducted by previous researchers, such as (Suprihatin et al, 2022), which studied the effect of motivation and discipline on teachers' performance, the result showed that motivation and discipline influenced the performance of madrasah teachers. Then, the research conducted by (Ahmad & Imam, 2022) researched how competence and career rewards can improve performance.…”
Section: Introductionmentioning
confidence: 97%